Evaluation of Comulative Average Student Grade against Average Student Grade of Freshmen as Gold Standard (Case Study of Bogor Agricultural University Students of 'Year' 30-'Year' 33) - Dian Handayani; Ahmad A. Mattjik; Asep Saefuddin (Forum Pasca Sarjana, 2002)
Degree of agreement between a given measurement method with gold standard method is often observed in a variety of field study. Laurent estimator, blended estimator, and agreement limit of 95% may be used as criteria to quantitythe degree of agreement among measurement methods.The degree of agreement between a cumulative average student grade of Bogor Agricultural University (IPB) students as an appropriate methods and their average student grade at freshman as a gold standard for the overall study programs in IPB among the students of 'year' 30 - 33 is varying. There are some study programs which are always belonging to low, intermediate, or high degree of agmment. Study Program of C02, C04, C05, and DO3 are always belonging to the low degree of agreement, Study Program of AOO, A03, A05, A08, BO1, D01, E02, and GO6 to the intermediate, and Study Program of A02, A07, F02, and GO1 to the high ones.